2015
DOI: 10.1371/journal.pone.0127585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trail-Cameras for Analyzing the Diet of Nesting Raptors Using the Northern Goshawk as a Model

Abstract: Diet studies present numerous methodological challenges. We evaluated the usefulness of commercially available trail-cameras for analyzing the diet of Northern Goshawks (Accipiter gentilis) as a model for nesting raptors during the period 2007–2011. We compared diet estimates obtained by direct camera monitoring of 80 nests with four indirect analyses of prey remains collected from the nests and surroundings (pellets, bones, feather-and-hair remains, and feather-hair-and-bone remains combined). In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…Contrary to our initial hypothesis, our results suggest that goshawks were either not dominant over buzzards in our study area or they exerted negligible dominance. This may explain why we did not observe a) predation by goshawks of buzzard nestlings or adults (García‐Salgado et al ), b) goshawks using nests built by buzzards, and c) buzzard nests showing larger‐than‐random separation from used goshawk nests during the study period. This lack of goshawk dominance contrasts with the situation in more northern European latitudes, where goshawks are larger than buzzards and often prey on buzzard nestlings and adults and occupy their nests (Kostrzewa , Krüger , Hakkarainen et al , Chakarov and Krüger , Björklund et al , Mueller et al ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Contrary to our initial hypothesis, our results suggest that goshawks were either not dominant over buzzards in our study area or they exerted negligible dominance. This may explain why we did not observe a) predation by goshawks of buzzard nestlings or adults (García‐Salgado et al ), b) goshawks using nests built by buzzards, and c) buzzard nests showing larger‐than‐random separation from used goshawk nests during the study period. This lack of goshawk dominance contrasts with the situation in more northern European latitudes, where goshawks are larger than buzzards and often prey on buzzard nestlings and adults and occupy their nests (Kostrzewa , Krüger , Hakkarainen et al , Chakarov and Krüger , Björklund et al , Mueller et al ).…”
Section: Discussionmentioning
confidence: 71%
“…The three species can also compete for food as they show some overlap in diet, with sparrowhawks and buzzards showing the less overlap (Tubbs , Newton , Cramp and Simmons , Kenward ). Goshawks feed on small‐sized birds with this component of the diet varying locally (Rutz et al ), even though the main components of their diet are usually medium‐sized birds and mammals, including raptors such as sparrowhawks and, especially in northern latitudes, buzzards (Kostrzewa , Krüger , García‐Salgado et al ). Thus, goshawks are super‐predators (Lourenço et al ) that may influence nest spacing of other forest‐dwelling raptors (Gamauf et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The camera traps also print relevant data on photographs and videos, such as time, date, and temperature (O'Brien and Kinnaird 2008). Camera traps have been successfully used, for example, to estimate the abundance of marked birds (O'Brien and Kinnaird 2008), to study habitat use (O'Brien and Kinnaird 2008, Srbek-Araujo et al 2012, Kuhnen et al 2013, diet (Renner et al 2012, García-Salgado et al 2015, social organization (Srbek-Araujo et al 2012), daily and seasonal activity patterns (Srbek-Araujo et al 2012, Kuhnen et al 2013, Dias et al 2016, nesting behavior (Rollack et al 2013), and in a few recent studies, they were used to identify nest predators (Knight et al 2014, Thiebot et al 2014, Davies et al 2015, Grendelmeier et al 2015. In studies that identified nest predators, the delay in triggering and the inability to detect small predators were the primary potential drawbacks impeding broader use of camera traps (O'Brien and Kinnaird 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the use of digital photography for dietary studies has included the use of camera‐traps to investigate the diet of nesting raptors (García‐Salgado et al . ; Robinson, Franke & Derocher ), and the combined use of digital compact cameras with spotting scopes (digiscoping) to assist prey identification (made primarily by observations) for Caspian terns ( Hydroprogne caspia ) and common murres ( Uria aalge ) (Larson & Craig ; Gladics et al . ).…”
Section: Introductionmentioning
confidence: 99%